2004
DOI: 10.1523/jneurosci.1842-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Reactive Oxygen Species in the Reaction Catalyzed by α-Ketoglutarate Dehydrogenase

Abstract: ␣-Ketoglutarate dehydrogenase (␣-KGDH), a key enzyme in the Krebs' cycle, is a crucial early target of oxidative stress (Tretter and Adam-Vizi, 2000). The present study demonstrates that ␣-KGDH is able to generate H 2 O 2 and, thus, could also be a source of reactive oxygen species (ROS) in mitochondria. Isolated ␣-KGDH with coenzyme A (HS-CoA) and thiamine pyrophosphate started to produce H 2 O 2 after addition of ␣-ketoglutarate in the absence of nicotinamide adenine dinucleotide-oxidized (NAD ϩ ). NAD ϩ , w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
309
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(328 citation statements)
references
References 65 publications
13
309
1
5
Order By: Relevance
“…PDHC is closely associated with Complex I of the electron transport chain [47] where much of the endogenous superoxide production is thought to occur. PDHC and α-ketoglutarate dehydrogenase complex may also be important sources of superoxide and, consequently, peroxynitrite [48,49]. The free radical pathways leading to nitration are initiated secondary to the reaction of peroxynitrite with carbon dioxide [50] and PDHC is one of the main sources of carbon dioxide within the mitochondria [51].…”
Section: Discussionmentioning
confidence: 99%
“…PDHC is closely associated with Complex I of the electron transport chain [47] where much of the endogenous superoxide production is thought to occur. PDHC and α-ketoglutarate dehydrogenase complex may also be important sources of superoxide and, consequently, peroxynitrite [48,49]. The free radical pathways leading to nitration are initiated secondary to the reaction of peroxynitrite with carbon dioxide [50] and PDHC is one of the main sources of carbon dioxide within the mitochondria [51].…”
Section: Discussionmentioning
confidence: 99%
“…While under conditions of inhibited electron transfer (e.g., under conditions of cytochrome c release), all these sites are potentially relevant, the relevance of the latter site under the conditions of uninhibited electron flow is still a matter of discussion (39,40). Additionally to the sites within mitochondrial respiratory chain, several flavoproteins in the mitochondrial matrix space, like the a-lipoamide dehydrogenase moiety of the a-ketoglutarate dehydrogenase complex (41,42) or the electron transfer flavoprotein of the b-oxidation pathway (37), are further candidate sites for mitochondrial superoxide production.…”
Section: Mitochondrial Formation Of Ros and Neurodegenerationmentioning
confidence: 99%
“…Independent studies have demonstrated that a-KGDH could be an important source of ROS (Starkov et al 2004;Tretter & Adam-Vizi 2004).…”
Section: A-kgdh As a Generator Of Oxidative Stressmentioning
confidence: 99%